Commemorative Issue in Honor of Professor Karlheinz Schwarz on the Occasion of His 80th Birthday - Chermette, Henry (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
A collection of 18 scientific papers written in honor of Professor Karlheinz Schwarz's 80th birthday. The main topics include spectroscopy, excited states, DFT developments, results analysis, solid states, and surfaces.